The relationship between cadence decline, cardiovascular drift and aerobic decoupling as a marker of fatigue in well trained cyclists - Barsumyan, A.; Soost, C.; Graw, J. A.; Burchard, R. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Prolonged steady-state cycling is characterised by gradual neuromuscular and metabolic acute fatigue, which may affect an athlete`s movement patterns. We hypothesize that athletes might unconsciously reduce cadence as a compensatory strategy to maintain power output. To test this theory, we examined changes in cadence and internal load during extended submaximal cycling.